EMPLOYMENT OPPORTUNITIES AND POVERTY LEVELS IN PRO V INSI KALIMANTAN TIMUR - Ditha Pradnya Puspita; Theresia Militina; Aji Sofyan Effendi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Poverty is one factor that concerns a country not least in Indonesia in general and East Kalimantan Province in particular. With the increasing number of poor people in an area being a bad impact on the performance of the government itself, so the government must be able to work to overcome and reduce the number of poor people in the area, one of which is providing opportunities for broad work for the community, the purpose of this study is to analyze several factors that can be used in reducing poverty. In this study there are several independent variables used including infrastructure spending, investment, transfer funds and economic growth and with the dependent variables which are dependent on employment opportunities and poverty levels. In this study using a tool such as SPSS version 22 where to see the direct or indirect relationship between the independent variables on the dependent variable. The analysis test results obtained that the independent variable as a whole has an influence on the employment variable and also on the poverty level variable, the independent variable has a positive and significant effect indirectly on the poverty level variable with the employment opportunity variable as an intermediary .